Query 3 

#$&*

course Mth 272

06/08 7 pm

Question: `q 4.5.5 (previously 4.5.10 (was 4.4.10)) find the derivative of ln(1-x)^(1/3) 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

1/3 ln(1-x)

 u'/u

-1/ (1-x) * 1/3

 

 

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

 

Note that ln(1-x)^(1/3) = 1/3 ln(1-x)

 

The derivative of ln(1-x) is u ' * 1/u with u = 1-x. It follows that u ' = -1 so the derivative of ln(1-x) is -1 * 1/(1-x) = -1/(1-x).

 

The derivative of 1/3 ln(1-x) is therefore 1/3 * -1/(1-x) = -1 / [ 3(1-x) ].**

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

------------------------------------------------

Self-critique Rating: Ok

*********************************************

Question: `q4.5.9 (previously 4.5.25 (was 4.4.24)) find the derivative of ln( (e^x + e^-x) / 2)

 

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

u'/u

((e^x + -e^.x)(2)/ 4) * (2/ (e^x + e^-x))

(e^x + -e^-x)/ (e^x + e^/x)

 

 

 Confidence Assessment: 3

 

.............................................

Given Solution:

 

`a the derivative of ln(u) is 1/u du/dx; u = (e^x + e^-x)/2 so du/dx = (e^x - e^-x) / 2.

 

The term - e^(-x) came from applying the chain rule to e^-x.

 

The derivative of ln( (e^x + e^-x) / 2) is therefore

 

[(e^x - e^-2) / 2 ] / ] [ (e^x + e^-x) / 2 ] = (e^x - e^-x) / (e^x + e^-x).

 

This expression does not simplify, though it can be expressed in various forms (e.g., (1 - e^-(2x) ) / ( 1 + e^-(2x) ), obtained by dividing both numerator and denominator by e^x.).

 

ALTERNATIVE SOLUTION:

 

ln( (e^x + e^-x) / 2) = ln( (e^x + e^-x) ) - ln(2).

 

the derivative of e^(-x) is - e^(-x) and ln(2) is constant so its derivative is zero.

 

So you get

 

y ' = (e^x - e^-x)/(e^x + e^-x). **

 

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 Self-critique Rating: Ok

*********************************************

Question: `q 4.5.10 (previously 4.5.30 (was 4.4.30) ) write log{base 3}(x) with base e

 

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

 

log base3 (x)= log x/ log 3 = ln x/ln3

 

  

 

 

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

 

`a

We know that

 

log{base b}(a) = log(a) / log(b), so that

log(a) = log(b) * log{base b}(a),

 

where the 'log' in log(a) and log(b) can stand for the logarithm to any base. 

 

In particular, if this 'log' stands for the base-e logarithm, we write it as 'ln' (which stands for 'natural log'), and we could write the above as

 

log{base b}(a) = ln(a) / ln(b).

 

The expression in the current problem can therefore be written as

 

log{base 3}(x) = ln(x) / ln(3).

 

It's worth noting also that

 

y = log{base 3}(x) means that x = 3^y; i.e., y is the power to which 3 must be raised to give us x.

 

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 Self-critique Rating: Ok

*********************************************

Question: `q4.5.22 (previously extra prob (was 4.4.50)). Find the equation of the line tangent to the graph of 25^(2x^2) at (-1/2,5)

 

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

a^x= a^x * lna

25^(2x^2) * ln25 * 4x

 

  

 

 

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

 

`a Write 25^u where u = 2x^2. So du/dx = 4x.

 

The derivative of a^x is a^x * ln(a). So the derivative of 25^u with respect to x is

 

du / dx * ln(25) * 25^u = 4x ln(25) * 25^u = 4x ln(25) * 25^ (2 x^2).

 

Evaluating this for x = -1/2 you get

 

4 * (-1/2) ln(25) * 25^(2 * (-1/2)^2 ) = -2 ln(25) * 25^(1/2) = -2 ln(25) * 5 = -10 ln(25) = -20 ln(5) = -32.189 approx.

 

So the tangent line is a straight line thru (-1/2, 5) and having slope -20 ln(5). The equation of a straight line with slope m passing thru (x1, y1) is

 

(y - y1) = m ( x - x1) so the slope of the tangent line must be

 

y - 5 =-20 ln(5) ( x - (-1/2) ) or

y - 5 = -20 ln(5) x - 10 ln(5). Solving for y we get

y = -20 ln(5) x - 10 ln(5).

 

A decimal approximation is

 

y = -32.189x - 11.095

 

ALTERNATIVE SOLUTION:

 

A straight line has form y - y1 = m ( x - x1), where m is the slope of the graph at the point, which is the value of the derivative of the function at the point. So you have to find the derivative of 25^(2x^2) then evaluate it at x = -1/2.

 

The derivative of a^x is ln(a) * a^x. The derivative of 25^z would therefore be ln(25) * 25^z. The derivative of 25^(2 x^2) would be found by the chain rule with f(z) = 25^z and g(x) = 2 x^2. The result is g ' (x) * f ' (g(x)) = 4 x * ln(25) * 25^(2x^2). Evaluating at x = -1/2 we get -2 ln(25) * 25^(1/2) = -10 ln(25).

 

Now we use the ponit-slope form of the equation of a straight line to get (y - 5) = -10 ln(25) * (x - (-1/2) ) and simplify. **

 

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 Self-critique Rating: Ok

*********************************************

Question: `q4.5.25 (previously 4.5.59 (was 4.4.59)) dB = 10 log(I/10^-16); find rate of change when I=10^-4

 

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

10(10^16/ln(10) ) / (I/ (10^-16))

 Plug in 10^-4 into I

43,429.45

 

 

  

 

 

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

 

`a This function is a composite; the inner function is I / 10^-16, which has derivative 1/10^-16 = 10^16. So the derivative is

 

dB' = dB / dI = 10 ( 10^16 * / ln(10) ) / (I / 10^-16) = 10 / [ ln(10) * I ].

 

Alternatively, 10 log(I / 10^-16) = 10 (log I - log(10^-16) ) = 10 log I + 160; the derivative comes out the same with no need of the chain rule.

 

Plugging in I = 10^-4 we get rate = 10 / [ ln(10) * 10^-4 ] = 10^5 / ln(10), which comes out around 40,000 (use your calculator to get the accurate result. **

 

STUDENT COMMENT

 

I did not know how to find the derivative once I simplified the problem. After viewing the solution, I am still confused.
INSTRUCTOR RESPONSE

 

log I = ln(I) / ln(10).
The derivative of ln(x) with respect to x is 1/x, so the derivative with respect to I of ln(I) is 1 / I.
So the derivative of ln(I) / ln(10) is (1 / I ) * (1 / ln(10) ) = 1 / (I ln(10) ).

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 Self-critique Rating: Ok

*********************************************

Question: `q4.5.26 (previously 4.5.60 (was 4.4.60)) T = 87.97 + 34.96 ln p + 7.91 `sqrt(p); find rate of change

 

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

 T= 0 + (34.96/p) + (3.955/ (p^(1/2))

 

 

  

 

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

 

`a The derivative with respect to p of ln p is 1 / p and the derivative with respect to p of sqrt(p) is 1 / (2 sqrt(p)). The derivative of the constant 89.97 is zero so

 

dT/dp = 34.96 * 1/p + 7.91 * 1 / (2 sqrt(p)) = 34.96 / p + 3.955 / sqrt(p). **

 

STUDENT QUESTION

 

Not understanding why the sqrt does not go away

 

INSTRUCTOR RESPONSE

 

The derivative with respect to p of sqrt(p) is 1 / (2 sqrt(p)).
This is a familiar derivative from first-semester calculus, obtained from the power-function rule that tells us that the derivative of x^a is a x^(a - 1). (this is usually stated with exponent p instead of a, but since p is the variable in this problem that form would almost certainly be confusing).
For example the derivative of x^3 is 3 * x^(3-1) = 3 x^2.
The derivative relevant to the current problem is the derivative of sqrt(x), or x^(1/2). The derivative is 1/2 * x^(1/2 - 1) = 1/2 x ^ (-1/2).
x^(-1/2) = 1 / x^(1/2) = 1 / sqrt(x). Therefore our derivative 1/2 x^(-1/2) is 1 / (2 sqrt(x)).
In the current problem the variable is p rather than x. The derivative, with respect to p, of p^(1/2) is 1/2 p^(1/2 - 1) = 1 / (2 sqrt(p) ).

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 Self-critique Rating: Ok

 

"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

*********************************************

Question: `q4.5.9 (previously 4.5.25 (was 4.4.24)) find the derivative of ln( (e^x + e^-x) / 2)

 

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

u'/u

((e^x + -e^.x)(2)/ 4) * (2/ (e^x + e^-x))

(e^x + -e^-x)/ (e^x + e^/x)

 

 

 Confidence Assessment: 3

 

.............................................

Given Solution:

 

`a the derivative of ln(u) is 1/u du/dx; u = (e^x + e^-x)/2 so du/dx = (e^x - e^-x) / 2.

 

The term - e^(-x) came from applying the chain rule to e^-x.

 

The derivative of ln( (e^x + e^-x) / 2) is therefore

 

[(e^x - e^-2) / 2 ] / ] [ (e^x + e^-x) / 2 ] = (e^x - e^-x) / (e^x + e^-x).

 

This expression does not simplify, though it can be expressed in various forms (e.g., (1 - e^-(2x) ) / ( 1 + e^-(2x) ), obtained by dividing both numerator and denominator by e^x.).

 

ALTERNATIVE SOLUTION:

 

ln( (e^x + e^-x) / 2) = ln( (e^x + e^-x) ) - ln(2).

 

the derivative of e^(-x) is - e^(-x) and ln(2) is constant so its derivative is zero.

 

So you get

 

y ' = (e^x - e^-x)/(e^x + e^-x). **

 

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 Self-critique Rating: Ok

*********************************************

Question: `q 4.5.10 (previously 4.5.30 (was 4.4.30) ) write log{base 3}(x) with base e

 

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

 

log base3 (x)= log x/ log 3 = ln x/ln3

 

  

 

 

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

 

`a

We know that

 

log{base b}(a) = log(a) / log(b), so that

log(a) = log(b) * log{base b}(a),

 

where the 'log' in log(a) and log(b) can stand for the logarithm to any base. 

 

In particular, if this 'log' stands for the base-e logarithm, we write it as 'ln' (which stands for 'natural log'), and we could write the above as

 

log{base b}(a) = ln(a) / ln(b).

 

The expression in the current problem can therefore be written as

 

log{base 3}(x) = ln(x) / ln(3).

 

It's worth noting also that

 

y = log{base 3}(x) means that x = 3^y; i.e., y is the power to which 3 must be raised to give us x.

 

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 Self-critique Rating: Ok

*********************************************

Question: `q4.5.22 (previously extra prob (was 4.4.50)). Find the equation of the line tangent to the graph of 25^(2x^2) at (-1/2,5)

 

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

a^x= a^x * lna

25^(2x^2) * ln25 * 4x

 

  

 

 

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

 

`a Write 25^u where u = 2x^2. So du/dx = 4x.

 

The derivative of a^x is a^x * ln(a). So the derivative of 25^u with respect to x is

 

du / dx * ln(25) * 25^u = 4x ln(25) * 25^u = 4x ln(25) * 25^ (2 x^2).

 

Evaluating this for x = -1/2 you get

 

4 * (-1/2) ln(25) * 25^(2 * (-1/2)^2 ) = -2 ln(25) * 25^(1/2) = -2 ln(25) * 5 = -10 ln(25) = -20 ln(5) = -32.189 approx.

 

So the tangent line is a straight line thru (-1/2, 5) and having slope -20 ln(5). The equation of a straight line with slope m passing thru (x1, y1) is

 

(y - y1) = m ( x - x1) so the slope of the tangent line must be

 

y - 5 =-20 ln(5) ( x - (-1/2) ) or

y - 5 = -20 ln(5) x - 10 ln(5). Solving for y we get

y = -20 ln(5) x - 10 ln(5).

 

A decimal approximation is

 

y = -32.189x - 11.095

 

ALTERNATIVE SOLUTION:

 

A straight line has form y - y1 = m ( x - x1), where m is the slope of the graph at the point, which is the value of the derivative of the function at the point. So you have to find the derivative of 25^(2x^2) then evaluate it at x = -1/2.

 

The derivative of a^x is ln(a) * a^x. The derivative of 25^z would therefore be ln(25) * 25^z. The derivative of 25^(2 x^2) would be found by the chain rule with f(z) = 25^z and g(x) = 2 x^2. The result is g ' (x) * f ' (g(x)) = 4 x * ln(25) * 25^(2x^2). Evaluating at x = -1/2 we get -2 ln(25) * 25^(1/2) = -10 ln(25).

 

Now we use the ponit-slope form of the equation of a straight line to get (y - 5) = -10 ln(25) * (x - (-1/2) ) and simplify. **

 

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 Self-critique Rating: Ok

*********************************************

Question: `q4.5.25 (previously 4.5.59 (was 4.4.59)) dB = 10 log(I/10^-16); find rate of change when I=10^-4

 

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

10(10^16/ln(10) ) / (I/ (10^-16))

 Plug in 10^-4 into I

43,429.45

 

 

  

 

 

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

 

`a This function is a composite; the inner function is I / 10^-16, which has derivative 1/10^-16 = 10^16. So the derivative is

 

dB' = dB / dI = 10 ( 10^16 * / ln(10) ) / (I / 10^-16) = 10 / [ ln(10) * I ].

 

Alternatively, 10 log(I / 10^-16) = 10 (log I - log(10^-16) ) = 10 log I + 160; the derivative comes out the same with no need of the chain rule.

 

Plugging in I = 10^-4 we get rate = 10 / [ ln(10) * 10^-4 ] = 10^5 / ln(10), which comes out around 40,000 (use your calculator to get the accurate result. **

 

STUDENT COMMENT

 

I did not know how to find the derivative once I simplified the problem. After viewing the solution, I am still confused.
INSTRUCTOR RESPONSE

 

log I = ln(I) / ln(10).
The derivative of ln(x) with respect to x is 1/x, so the derivative with respect to I of ln(I) is 1 / I.
So the derivative of ln(I) / ln(10) is (1 / I ) * (1 / ln(10) ) = 1 / (I ln(10) ).

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 Self-critique Rating: Ok

*********************************************

Question: `q4.5.26 (previously 4.5.60 (was 4.4.60)) T = 87.97 + 34.96 ln p + 7.91 `sqrt(p); find rate of change

 

 

YYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYYY

Your solution:

 T= 0 + (34.96/p) + (3.955/ (p^(1/2))

 

 

  

 

confidence rating #$&*: 3

^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^^

.............................................

Given Solution:

 

`a The derivative with respect to p of ln p is 1 / p and the derivative with respect to p of sqrt(p) is 1 / (2 sqrt(p)). The derivative of the constant 89.97 is zero so

 

dT/dp = 34.96 * 1/p + 7.91 * 1 / (2 sqrt(p)) = 34.96 / p + 3.955 / sqrt(p). **

 

STUDENT QUESTION

 

Not understanding why the sqrt does not go away

 

INSTRUCTOR RESPONSE

 

The derivative with respect to p of sqrt(p) is 1 / (2 sqrt(p)).
This is a familiar derivative from first-semester calculus, obtained from the power-function rule that tells us that the derivative of x^a is a x^(a - 1). (this is usually stated with exponent p instead of a, but since p is the variable in this problem that form would almost certainly be confusing).
For example the derivative of x^3 is 3 * x^(3-1) = 3 x^2.
The derivative relevant to the current problem is the derivative of sqrt(x), or x^(1/2). The derivative is 1/2 * x^(1/2 - 1) = 1/2 x ^ (-1/2).
x^(-1/2) = 1 / x^(1/2) = 1 / sqrt(x). Therefore our derivative 1/2 x^(-1/2) is 1 / (2 sqrt(x)).
In the current problem the variable is p rather than x. The derivative, with respect to p, of p^(1/2) is 1/2 p^(1/2 - 1) = 1 / (2 sqrt(p) ).

 

&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&&

Self-critique (if necessary):

 Self-critique Rating: Ok

 

"

Self-critique (if necessary):

------------------------------------------------

Self-critique rating:

#*&!

&#Your work looks good. Let me know if you have any questions. &#